KEEFEKTIFAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD NEGERI 1 GODONG PADA TEMA INDAHNYA KERAGAMAN DI NEGERIKU - Kartika Cahya Lestari; Ferina Agustini; Mira Azizah (Universitas Negeri Medan, 2021)
Abstract: The Effectiveness ofModel Problem Based Learning on Critical Thinking Ability of Fourth Grade Students of SD Negeri 1 Godong on the Theme of the Beauty of Diversity in My Country. The purpose of this study was to determine the effectiveness of themodel Problem Based Learning on the critical thinking skills of fourth grade students of SD Negeri 1 Godong on theme 7